Epidemiological profile of maternal deaths due to postpartum hemorrhage in Brazil between 2000 and 2023 (Research, Society and Development, 2025)
Introduction: Postpartum hemorrhage (PPH), an important cause of maternal mortality, is preventable but continues to affect women due to complications and inadequate diagnosis. Objective: To analyze the epidemiological profile of maternal deaths due to PPH in Brazil from 2000 to 2023. Methodology: Ecological, time-series study with a quantitative approach, carried out with secondary data from the Mortality Information System (SIM) of the Ministry of Health. The units of analysis were the 26 states and the Federal District of Brazil. The study population comprised all maternal deaths registered in the SIM, whose cause according to ICD-10 was O72 - PPH. Descriptive statistics were used in the analysis of nominal and ordinal categorical variables. There was no need for assessment by the CEP/CONEP System and the guidelines of the STROBE initiative were considered. Results: A total of 2,405 deaths from PPH in Brazil were analyzed, with an increase in notifications in 2015 and 2018. From 2016 onwards, deaths began to decrease. Most deaths occurred during the puerperium (57%), mainly affecting women between 20 and 39 years old, with low levels of education, and most deaths occurred in hospitals. Conclusion: Maternal mortality from PPH in Brazil is associated with failures in the health system, especially in filling out death records, and the low quality of prenatal care. Strengthening health education and professional training are essential to improve care for pregnant women and reduce mortality rates.